2019
DOI: 10.1021/acsomega.9b03003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substituents on the Properties of Metal-Free MRI Contrast Agents

Abstract: Materials possessing electron spin can shorten the T1 relaxation times in magnetic resonance imaging (MRI). For example, gadolinium (Gd) complexes with seven f-orbital electrons are widely used as contrast agents in clinical applications. However, Gd has severe potential side effects, and thus metal-free alternatives are needed. Toward this end, we synthesized seven NO radicals consisting of a dioxa-azaspiro[4.5]decane framework having various substituents, DAD-X (X = methyl, ethyl, n-propyl, c-propyl, vinyl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…BNA‐BuTEMPO contains the TEMPO radical, a well‐known stable organic radical, which is widely used as a spin source for molecular magnets, [23, 24] metal‐free MRI contrast agents, [25–28] and as a reactive agent for oxidation reactions [29] and lipid radicals [30] . To verify the aggregation behavior, the TEMPO radical was introduced into the BNA framework.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BNA‐BuTEMPO contains the TEMPO radical, a well‐known stable organic radical, which is widely used as a spin source for molecular magnets, [23, 24] metal‐free MRI contrast agents, [25–28] and as a reactive agent for oxidation reactions [29] and lipid radicals [30] . To verify the aggregation behavior, the TEMPO radical was introduced into the BNA framework.…”
Section: Resultsmentioning
confidence: 99%
“…NPs of 50–500 nm in size can accumulate in tumor tissue via the enhanced permeability retention (EPR) effect [3, 31] . Organic radicals such as TEMPO analogs have been developed as metal‐free MRI contrast agents [25–28] replacing Gd‐based agents; [33–36] thus, the radical‐based NPs are expected to behave as metal‐free MRI contrast agents capable of accumulating tumors. In addition, by embedding drugs in NPs, the construction of therapeutic and diagnostic (theranostic) materials for fluorescence imaging and MRI using BNA‐X is possible, and studies in this area are currently underway.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of small radical species with fast molecular motion such as DAD-X (Scheme 1), the intensities of the three corresponding signals should be identical (Figure 1, right). 27 However, in slower-motion molecules, such as the radical polymers, the three line intensities become distinguishable. 23−26 The signal in the highest field yielded the lowest intensity and was broadened, indicating that the rotational correlation time (τ R ) was prolonged by the formation of the RNPs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The log P values indicate the hydrophilicity and hydrophobicity of the compounds, and these values are frequently used to explain the interactions between drugs and receptors in pharmaceutical sciences. We recently reported 27 a significant relationship between the log P and r 1 values when using several different radical species having polar or nonpolar substituents (DAD-X in Scheme 1). We found that the r 1 value depended remarkably on the log P value, and the radical species with lower log P values (i.e., hydrophilic species) yielded higher r 1 values than those with high log P values (i.e., hydrophobic species).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another similar approach to the synthesis of SNRs of the PROXYL type, which contain an easily modifiable 1,3-dioxane moiety in the spiro substituent, was implemented in the work of Japanese researchers in 2019. Based on 2-bromo-2-nitropropane-1,3-diol 218 , 2,2-dimethyl-5-nitro-1,3-dioxane was synthesized, and then consecutively by Michael and Grignard additions, it was transformed through intermediate nitrone 219 into 5-R-substituted SNRs 220a-g ( Scheme 39 ) [ 149 ]. The study also described the physical properties of synthesized SNRs 220 , e.g., log P and water−proton relaxivity ( r 1 , a measure of the ability to serve as a contrast agent), and the reactivity ( k 2 ) of these species toward ascorbic acid (AsA) was evaluated.…”
Section: 25-dihydropyrrole (3-pyrroline)- and Pyrrolidine (Proxylmentioning
confidence: 99%